2012
DOI: 10.3389/fpls.2012.00171
|View full text |Cite|
|
Sign up to set email alerts
|

Iron biofortification and homeostasis in transgenic cassava roots expressing the algal iron assimilatory gene, FEA1

Abstract: We have engineered the tropical root crop cassava (Manihot esculenta) to express the Chlamydomonas reinhardtii iron assimilatory gene, FEA1, in its storage roots with the objective of enhancing the root nutritional qualities. Iron levels in mature cassava storage roots were increased from 10 to 36 ppm in the highest iron accumulating transgenic lines. These iron levels are sufficient to meet the minimum daily requirement for iron in a 500 g meal. Significantly, the expression of the FEA1 gene in storage roots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 77 publications
0
12
0
1
Order By: Relevance
“…Next generation sequencing information has allowed genome sequencing of the most important crops to human consumption. There has also been progress in identifying genes that are involved in the movement of Fe and Zn in plants and using these genes for biofortification of rice (Goto et al, 1999), cassava (Ihemere, 2012), wheat (Borg et al, 2012), maize (Kanobe et al, 2013), lettuce (Goto et al, 2000) and soybean (Vasconcelos et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Next generation sequencing information has allowed genome sequencing of the most important crops to human consumption. There has also been progress in identifying genes that are involved in the movement of Fe and Zn in plants and using these genes for biofortification of rice (Goto et al, 1999), cassava (Ihemere, 2012), wheat (Borg et al, 2012), maize (Kanobe et al, 2013), lettuce (Goto et al, 2000) and soybean (Vasconcelos et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…All commonly used genetic transformation systems in cassava rely on the induction of somatic embryogenesis. In some cases, OES produced from explants is used directly for transgene integration (Ihemere et al, 2012;Ntui et al, 2015). Alternatively, OES can be matured to generate caulogenic cotyledon tissues (Jorgensen et al, 2005;Li et al, 1996), or converted to a highly disorganized FEC, which can then be subjected to Agrobacterium or direct gene transfer technologies (Liu et al, 2011;Taylor et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Constructs p718, p5001 and p5003 consisted of inverted repeat sequences from the CP genes of UCBSV (p718), CBSV (p5003) and both CPs (p5001). pRS26 was designed to elevate iron content in cassava storage roots by expression of the FEA1 gene under control of the Patatin type-1 promoter (Ihemere et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Previously it was shown that transgenic expression of FEA1, from the unicellular algae Chlymadomonas reinhardtii, resulted in a threefold accumulation of iron in greenhouse-grown cassava storage roots [38]. FEA1 functions as an iron assimilatory protein and complements the Arabidopisis irt1 mutant [68] and is thought to enhance iron uptake and transport from the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the iron-specific assimilatory protein FEA1 from Chlamydomonas reinhardtii was integrated into cassava and expressed under control of the storage organ specific type I patatin promoter. Regenerated plants showed an approximate three-fold increase in iron in their storage roots compared with the non-transgenic control plants when grown under greenhouse conditions [38]).…”
Section: Introductionmentioning
confidence: 99%